Vitronectin promotes immunothrombotic dysregulation in the venular microvasculature - Uhl, Bernd; Haring, Florian; Slotta-Huspenina, Julia; Luft, Joshua; Schneewind, Vera; Hildinger, Jonas; Wu, Zhengquan; Steiger, Katja; Smiljanov, Bojan; Batcha, Aarif M. N.; Keppler, Oliver T.; Hellmuth, Johannes C.; et al. (Frontiers in Immunology, 2023)
Microvascular immunothrombotic dysregulation is a critical process in the pathogenesis of severe systemic inflammatory diseases. The mechanisms controlling immunothrombosis in inflamed microvessels, however, remain poorly understood. Here, we report that under systemic inflammatory conditions the matricellular glycoprotein vitronectin (VN) establishes an intravascular scaffold, supporting interactions of aggregating platelets with immune cells and the venular endothelium. Blockade of the VN receptor glycoprotein (GP)IIb/IIIa interfered with this multicellular interplay and effectively prevented microvascular clot formation. In line with these experimental data, particularly VN was found to be enriched in the pulmonary microvasculature of patients with non-infectious (pancreatitis-associated) or infectious (coronavirus disease 2019 (COVID-19)-associated) severe systemic inflammatory responses. Targeting the VN-GPIIb/IIIa axis hence appears as a promising, already feasible strategy to counteract microvascular immunothrombotic dysregulation in systemic inflammatory pathologies.